2021
DOI: 10.1111/njb.03053
|View full text |Cite
|
Sign up to set email alerts
|

Strobilanthes pushpagiriensis (Acanthaceae): a new species from Western Ghats, India

Abstract: A new species of Strobilanthes collected from Pushpagiri Wildlife Sanctuary, Karnataka, India is described here as S. pushpagiriensis. It is closely allied to S. anamallaica and S. ciliata in having two distinct small leafy bracts at the middle of the peduncle, but differs from them in having dense grayish-white hairs throughout, linear-lanceolate leaves with 9-11 pairs of secondary veins, 2-3 spikes per peduncle and linear-lanceolate densely glandular hairy bracts. Detailed description, distribution, conserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Thus, giving good criteria to recognize each species studied. A previous study conducted by Patil & Patil (2011) on 22 species of the family Acanthaceae reported the presence of hypostoma-tic and diacytic stomata. Besides, preliminary studies by Metcalfe & Chalk (1965) also recorded the presence of diacytic type stomata either on both surfaces of the epidermis (amphistomatic) or on the apical epidermal layer only (hypostomatic), thereby giving evidence of the presence of amphistomatic and diacytic type of stomata in all species studied.…”
Section: Asystasia Gangetica Subsp Micrantha Rhinacanthus Nasutusmentioning
confidence: 94%
“…Thus, giving good criteria to recognize each species studied. A previous study conducted by Patil & Patil (2011) on 22 species of the family Acanthaceae reported the presence of hypostoma-tic and diacytic stomata. Besides, preliminary studies by Metcalfe & Chalk (1965) also recorded the presence of diacytic type stomata either on both surfaces of the epidermis (amphistomatic) or on the apical epidermal layer only (hypostomatic), thereby giving evidence of the presence of amphistomatic and diacytic type of stomata in all species studied.…”
Section: Asystasia Gangetica Subsp Micrantha Rhinacanthus Nasutusmentioning
confidence: 94%
“…The characteristic features of the family Acanthaceae are the presence of cystoliths in leaf lamina and petiole. But in J. beddomei these characteristic cystoliths are absent 15 . There is no further anatomical or pharmacognostical studies about this plant reported yet.…”
Section: Pharmacognosymentioning
confidence: 96%
“…These crystals form an essential component in the taxonomic account of Acanthaceae, as this is the only family found within the Lamiales that comprise of cystoliths . They differ in nature, size, shape, colour, and occurrence throughout the family and can occur singly, double or triple (Patil and Patil, 2011). Cystoliths, can serve as a deterrent against insects and large grazing herbivores, and the quantity of the crystals can determine defence resilience and efficiency (da Costa et al, 2009).…”
Section: Taxonomy and Historical Reviewmentioning
confidence: 99%
“…Cystoliths, can serve as a deterrent against insects and large grazing herbivores, and the quantity of the crystals can determine defence resilience and efficiency (da Costa et al, 2009). The occurrence of cystoliths and stomata which are caryophyllaceous in Acanthaceae, is a diagnostic characteristic to the family (Inamdar, 1970;Patil and Patil, 2011;.…”
Section: Taxonomy and Historical Reviewmentioning
confidence: 99%